The Influence of Accountability and Transparency on Public Trust in Villages Mediated by Internal Control Systems in Sidoarjo - Ryandi, Ninesia Aliya; Sari, Rida Perwita (Dinasti Publisher, 2024)
This study aims to investigate the relationship between accountability, transparency, internal control systems, and community trust in villages in Sidoarjo Regency. The background of this research is based on the importance of the role of the Village Consultative Body (BPD) as a government institution at the village level in ensuring accountability, transparency, and the effectiveness of internal controls to enhance community trust. The research method used is quantitative by collecting data from BPD members and representatives of the village community through questionnaires. The results of data analysis show that accountability, transparency, and internal control systems have a significant positive effect on community trust. Furthermore, it was found that the internal control system can mediate the relationship between accountability and transparency with community trust. These findings provide a deeper understanding of the importance of implementing accountability, transparency, and internal control practices in building community trust in government institutions at the village level.